DALIT DISABLED WOMEN'S DISCOURSE: AN ANALYTICAL STUDY - Mishra, Om (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Hindi literature, since the last few years, women's discourse,1 Dalit discourse2 and tribal discourse3 are emerging as new discourses. On one hand, there is an opportunity to bring the marginalized community into the mainstream and on the other hand, Hindi literature has also flourished. Sahila is the mirror of society, so it is certain that the reflection of women, Dalits, tribes and other communities should be visible in it. Since the last few years, the concept of social inclusion4 has forced us to think about the most neglected people of the society. As a result, a new thinking has been formed towards Dalits, women, tribal people as well as disabled people. Whether it has developed as a result of protest or as a result of judicial process or as a result of the concept of social justice, it has succeeded to a great extent in bringing the people of Shamia into the mainstream. It has come to the fore that these people should also be given equal access to the resources of the country and be brought into the mainstream and contribute equally to the development of the country step by step.